Integrated Approach in Teaching Language between Theory and Practice - Bani Yaseen, Mohammad Fawzy; Alzu’bi, Mohammad Akram; Al-Tawalbeh, Ali Mahmoud (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed at studying the integrated approach in teaching language between theory and practice. To achieve the purpose of the study, the researchers designed a model of whole- language approach, Language experience approach, whole text approach, the cognitive academic approach, then, they designed a comprehensive model for an integrated approach to recognize the nature of this approach. The study relied on an analytical descriptive approach. So, it described the integrated approach, analyzed its structure, and clarified the relationship between its elements. Based on the findings of the study, the researchers recommends to curry out experimental studies and training courses to recognize the effectiveness of the integrated approach, and including the importance of integrated approach in the students’ curricula.
Keywords: Language; Teaching; Integrated approach